PENGARUH COMPUTER-ASSISTED LANGUAGE LEARNING (CALL) TERHADAP KEMAMPUAN READING COMPREHENSION MAHASISWA PROGRAM STUDI TEKNIK INFORMATIKA DI UNIVERSITAS ISLAM BALITAR - Primasari, Yusni (Universitas Islam Balitar, 2019)
In general, the skills in mastering English are reading, speaking, listening, and writing. Of these four things, reading is an important factor that supports the process of mastering other skills and increasing knowledge. Based on the results of the pretest to students of the Informatics Engineering Study Program, the researcher concluded that their grades were low with an average of 47,28. Furthermore, the Indonesian government has recommended the use of CALL by establishing national education development planning. Based on this, the researcher took advantage of the use of gadgets, in this case, a computer or laptop in language learning called CALL. This study adopted a pre-experimental design. The pretest is used to get scores before treatment. Treatment is given to the group for a specified time. After that, the researcher gives a post-test. The results of calculations using the t-test found that the t-value obtained was 7,726 while the critical t-value required at p> 0,05 the level of significance of two-tailed tests was 2,060 (df = 25), p> 0,01 significant level of two-tailed the test was 2,787 (df = 25), p> 0,001 the significant level of the two-tailed tests was 3,725 (df = 25). The results of this study indicate there are difference in scores on pre-test and post-test. So it can be said that students who are taught with CALL achieve better reading comprehension than those taught by printed text